Hematopoietic progenitor cell mobilization for autologous transplantation - a literature review - Salvino,Marco Aurélio (2016)
ABSTRACT The use of high-dose chemotherapy with autologous support of hematopoietic progenitor cells is an effective strategy to treat various hematologic neoplasms, such as non-Hodgkin lymphomas and multiple myeloma. Mobilized peripheral blood progenitor cells are the main source of support for autologous transplants, and collection of an adequate number of hematopoietic progenitor cells is a critical step in the autologous transplant procedure. Traditional strategies, based on the use of growth factors with or without chemotherapy, have limitations even when remobilizations are performed. Granulocyte colony-stimulating factor is the most widely used agent for progenitor cell mobilization. The association of plerixafor, a C-X-C Chemokine receptor type 4 (CXCR4) inhibitor, to granulocyte colony stimulating factor generates rapid mobilization of hematopoietic progenitor cells. A literature review was performed of randomized studies comparing different mobilization schemes in the treatment of multiple myeloma and lymphomas to analyze their limitations and effectiveness in hematopoietic progenitor cell mobilization for autologous transplant. This analysis showed that the addition of plerixafor to granulocyte colony stimulating factor is well tolerated and results in a greater proportion of patients with non-Hodgkin lymphomas or multiple myeloma reaching optimal CD34+ cell collections with a smaller number of apheresis compared the use of granulocyte colony stimulating factor alone.